STUDENTS’ AWARENESS OF LANGUAGE USE AND LANGUAGE KNOWLEDGE ON EFL LEARNERS - Fadilatul _ HUDA (Journal of English Education, 2020)
This research was conducted because the researchers found that there was a language development program where students were required to use English on certain days, that is monday and tuesday. Based on preminary research, the research found some problems that occur in the use of language and language knowledge in VIII class at Mts Sumatera Thawalib Parabek. There are: some students just talked without paying attention to the correct sentences and students rarely used English for communication or interaction. The design of this research was descriptive quantitative. The sample was collected from 57 students of VIII grades of Mts Sumatera Thawalib Parabek which used purposive sampling as the data was done by identfying the respondents’ responses. The result showed that the mean score of students’ awareness of language use has a good enough awareness which score is 58,74%. Furthermore, students’ awareness of language knowledge has a good awareness which score is 68,98%.